Indigenous child welfare in British Columbia : training and practice shifts in child protection - Thompson, Susan A. (Author); Hall, Wenona (Committee member); Chan, Adrienne (Committee member); Hogg, John (Chair); University of the Fraser Valley Social Work and Human Services (Degree granting institution) (University of the Fraser Valley, 2020)
In the Province of British Columbia there is an alarming over-representation of Indigenous children in the foster care system. An extensive literature review revealed there are policy and practice changes designed to address this problem. There are currently 24 Delegated Aboriginal Agencies throughout the province, each with varying levels of delegated authority. As well there are frameworks of practice, such as the Aboriginal Policy and Practice Framework created by the Ministry of Children and Family Development, the Nlaka’pamux Framework of Practice created by Scw’exmx Child and Family Services Society and the Syilx Child and Family Plan created by Okanagan Nation Alliance. These frameworks encourage child welfare practices that are more aligned with and culturally sensitive to Indigenous community(s) being served. There are also legislative changes such as Bill C-92 which was passed in June 2019; this is a Federal Act with the respect to First Nations, Inuit and Metis children, youth and family that encourages increased Indigenous jurisdiction over child welfare for Indigenous communities. The findings are that although there have been policy and practice changes made there remains to be an over-representation of Indigenous children in Foster Care and in fact in some cases the number of Indigenous children has risen. Indigenous child welfare British Columbia Delegated Aboriginal Agencies AOPSI CFCSA Frameworks Federal Legislation